Genetic relationships of three Yukon caribou herds determined by DNA typing - Zittlau, Keri; Coffin, John; Farnell, Richard; Kuzyk, Gerald; Strobeck, Curtis (Rangifer, 2000)
In this paper we examine genetic relationships of caribou (Rangifer tarandus caribou) in the Aishihik, Chisana, and Wolf Lake herds in the Yukon using DNA fingerprinting. The assignment test used in this analysis showed that the caribou herds were distinct. This finding is consistent with movement data from radio-collared caribou which demonstrates home range fidelity. We found a high level of heterozygosity and a genetic basis for population boundaries. DNA fingerprinting may provide an effective means to compare ecological and genetic relationships.